Bioherm Petroleum Reservoir Types and Features in Main Sedimentary Basins of the South China Sea - 许红 孙晶 廖晶 董刚 刘金庆 宋红瑛 王振峰 孙志鹏 金庆焕 张莉 朱玉瑞 赵新伟 (Journal of earth science (Wuhan, China), 2012)
It is known from macrocomparisons and microresearches of bioherm reservoirs in main sedimentary basins of the South China Sea through deep-water petroleum explorations and by means of 2D/3D seismic data and a whole-coring core from the Xisha Islands that there are great dif- ferences between deep-sea oil and gas fields in the world and those in the South China Sea, as reservoir systems of the former are mainly clastic rocks, whereas the latter have organic reefs that act as reser- voirs of their largest oil and gas fields, which are represented by large Liuhua 11-1 reef oilfield in the north and super-large L reef gas field in the south of the South China Sea. Therefore, it is of great significance to study deep-water hioherm reservoirs in the South China Sea. Comparisons of organic reefs in the four large islands of the South China Sea give evidences that such reefs in main sedimentary basins came into being during Cenozoic, especially in Neogene, and mainly occur as tower （point） reef, massive reef, platform-edge reef, and patch reef in shape, which show different reservoir physical properties and seismic reflection configurations and make up carbonate rock-bioherm formations in the island reef and sedimentary basin areas. Generally, the south and north parts differ from the east and the west of the South China Sea in geologic conditions, as their corresponding continental shelf/island shelf areas are relatively wide/ narrow, large stream current systems are well developed/not so well developed, and terrigenous sediments are relatively sufficient/insufficient. The southeast and south parts of the South China Sea had organic reefs built up earlier than the north and the reef building mainly took place in Neogene; these Neogene organic reefs all be- long to plant algal reef rocks. Liuhua oilfield in the Pearl River Mouth basin is found to mainly have red algal bindstone, Malampaya reef in the northern Palawan basin is rich in both red algal bind- stone and green algal reef segmented rock, and especially Miocene red algal framestone and green algal segmented rock are discovered in the Xisha Islands. These algal reefs created different sedimentary mi- crofacies as well as various rock structures and types, and through recent researches on the mechanism of dolomitization, freshwater dolomite was discovered and grouped under products from dolomitization in mixed water that was regression reefal dolomite of good reservoir properties.